FAKTOR-FAKTOR KUALITAS LINGKUNGA FAKTOR-FAKTOR KUALITAS LINGKUNGAN KERJA DENGAN GANGGUAN KESEHATAN SICK BUILDING SYNDROME (SBS) PADA PEGAWAI DI KANTOR RUMAH SAKIT GRANDMED LUBUK PAKAM: FAKTOR-FAKTOR KUALITAS LINGKUNGAN KERJA DENGAN GANGGUAN KESEHATAN SICK BUILDING SYNDROME (SBS) PADA PEGAWAI DI KANTOR RUMAH SAKIT GRANDMED LUBUK PAKAM - efrata sembiring; Yunita Syahputri Damanik (Jurnal Inovasi Kesehatan Masyarakat, 2026)
Background : Based on 500 indoor air quality investigations that have been conducted in the last decade, the National Institute for Occupational Safety and Health (NIOSH) found the main sources of indoor air quality problems including the presence of sources of contamination in the room (16%), contamination originating from from outdoors (10%), microbes (5%), building materials used (4%) and others (13%). The Indonesian Association of Public Health Experts/FKM conducted research on 350 employees from 18 companies in the DKI Jakarta area during July-December 2020. Based on the results of this study, 50% of people working in office buildings experience SBS. Method : This type of research is an analytic survey observation with cross-sectional the number of samples in this study as many as 45 people. The sampling technique of this study was simple random sampling with the chi-square test and determination of the prevalence ratio (PR). Results : The physical condition of the quality of the work environment met the requirements on the variables temperature (p-value = 0.229 ), lighting (p-value = 0.001), humidity (p-value = 0.033). Conclution : There is no effect between temperature and SBS, there is an effect between lighting and humidity with SBS.